Induction of alkaline phosphatase in Escherichia coli: effect of procaine hydrochloride. - Tribhuwan, R C (1977)
The effect of procaine hydrochloride, an anesthetic known to alter membrane structure, on the induced formation of alkaline phosphatase, a periplasmic enzyme, in Escherichia coli was investigated. Procaine hydrochloride specifically arrested the appearance of active alkaline phosphatase while permitting the induction of another enzyme, beta-galactosidase, which is internally localized. Evidence has been obtained to show that procaine hydrochloride does not arrest synthesis of inactive monomer subunits of the enzyme, indicating that the drug interferes in the conversion of monomer subunits to an active dimer enzyme.